Kahoot in Teams Games Tournament to Improve Elementary School Students' Learning Engagement - Yulia Yulia; Winda Andriani; Wawan Krismanto (Action Research Journal Indonesia (ARJI), 2025)
Learning motivation is a crucial factor in determining students' learning success, and this has not been seen optimally in SDN 3 Barru, South Sulawesi. Therefore, carryinga class action to overcome this problem. This study's essential purpose was to determine whether integrating Kahoot in the team's games tournament (TGT) model can improve students' learning process and engagement. The type of research is classroom action with a qualitative approach. The research subjects were 20 people, consisting of 1 teacher and 19 students. Data collection through observation and documentation. Analysis techniques through the stages of condensation, presentation, and conclusion. It was carried out in 2 cycles, with two meetings in each cycle. In cycle I, student engagement showed development and interest in participating in learning. However, it is not yet optimal. In cycle II, students who achieve a good level of learning engagement increased significantly, from 61% to 89%. As seen from the characteristics of students who are ready to receive learning, concentrate on following learning, the ability to remember material, actively fight in games, work together well in completing teacher/group assignments and in contributing value to the group. Integrating interactive digital media like Kahoot with a collaborative approach like TGT can create structured, meaningful, and enjoyable learning. The conclusion is that integrating Kahoot into the TGT learning model can improve the learning process and students engagement.